Innowacje w działalności bankowej w świetle przeciwdziałania zjawisku wykluczenia finansowego w Polsce - Cichowicz, Ewa; Nowak, Agnieszka K. (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
The goal of this article is to answer the question on the importance of innovations introduced by banks in Poland from the perspective of counteracting the processes related to financial exclusion of social groups. Conseąuently, selected innovative Solutions have been considered, contributing to improving the availability of banks’ offer. To accomplish this goal, we conducted an in-depth analysis of the subject literature. On this basis, the most important concepts for the subject - innovation and financial exclusion - were analysed. Subseąuently, the content of the websites of selected banks operating in Poland was reviewed. Thanks to this, it was possible to identify innovations that could help to limit financial exclusion. In addition, information of what methods and tools are used by other institutions (including international ones) in the fight against financial exclusion were also used